Investigation of the serum glucocorticoid kinase 1 gene in patients with transient tachypnea of the newborn. (July 2013) - Oztekin, Osman; Akyol, Mahmut; Kalay, Salih; Tezel, Gonul; Akcakus, Mustafa; Oygur, Nihal
Abstract Objective: The aim of this study was to investigate whether there is a role of the serum glucocorticoid kinase (SGK) 1 gene, which has an effect on the control of the epithelial sodium channels. Materials and method: This study included patients who were diagnosed with transient tachypnea of the newborn (TTN) with more than 37 weeks of gestation. As the control group, healthy newborns of the same gestational age were included. From each group, within the first 5 d of their lives, 2 cc of whole blood was taken in EDTA tubes, and stored at −80 °C. The DNA extraction was performed. Results: There were 32 patients in the TTN, and also 32 patients in the control group. The heterozygous allele rs1057293 (3/28) and rs1743966 (8/28) were located in the encoder region of the SGK 1 gene. In addition, in encoding region of the SGK 1 gene, the Arg97Ile (1/28), which causes the amino acid changes, had a genotype frequency of 0.0357, and a mutation was identified in Arg97Ile. Discussion: We have defined polymorphisms rs1057293 and rs1743966 in the SGK 1 gene, and the Arg97Ile mutation, for the first time in patients with TTN. This pilot study gave us some clues about a genetic basis of TTN phenotype, next to the lack of the pulmonary maturation.